Enhancement of the Dielectric and Energy Storage Properties of Lead-Free BNSLT Ceramics by Zr 4+ Substitution into B-Sites - Anupong Luangpangai; Nachtarika Noiphoowiang; Pathit Premwichit; Metarsit Klinbanmor; Naratip Vittayakorn; Aurawan Rittidech; Theerachai Bongkarn (Integrated ferroelectrics, 2023)
Abstract(Bi0.38Na0.30Sr0.28)0.98La0.02Ti1-xZrxO3 (abbreviated as BNSLT1-xZrx, with x = 0 − 0.05) lead free ceramics were fabricated using the solid-state combustion method. The phase structure, microstructure and electrical properties of the ceramics were investigated. The coexistence of the rhombohedral (R) and tetragonal (T) phases was found in all samples. Rietveld refinement confirmed that as x increased from 0 to 0.05, the rhombohedral phase increased from 41 to 60%. A nearly equal R:T phase ratio of 49:51 was obtained for x = 0.01. All ceramics displayed polygonal grain shapes with anisotropic grain growth. The average grain size of the ceramics was in the range of 0.46–0.79 µm. The optimal Zr4+ content resulted in increased grain growth and reduced pores, leading to improved electrical properties. The highest density (5.52 g/cm3), maximum dielectric constant (εm=2156), maximum polarization (Pmax=15.36 µC/cm2) and high energy storage properties (Wtotal=0.49 J/cm3, Wrec=0.45 J/cm3, Wloss=0.05 J/cm3 and η = 90.54% at 60 kV/cm) were obtained from x = 0.01 caused by a morphotropic phase boundary (MPB) and good morphology.Keywords: BNT-basedphase structuremicrostructuredielectricferroelectric AcknowledgmentsThe authors thank the Department of Physics, Faculty of Science, Naresuan University for their supporting facilities and Prof. Dr. David P. Cann, Oregon State University, for his assistance with polarization-electric field (P-E) hysteresis loop measurements. Thanks, are also given to Asst. Prof. Dr. Kyle V. Lopin for his help in editing the manuscript.Disclosure StatementNo potential conflict of interest was reported by the author(s).Additional informationFundingThis work was supported by The National Science, Research and Innovation Fund (NSRF) through Naresuan University [R2565B059]. The work of N. Vittayakorn was supported by KMITL through [Grant No. KREF116501].
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Multiferroics and related materials